High-Pressure Processing and Ultrasonication of Minimally Processed Potatoes: Effect on the Colour, Microbial Counts, and Bioactive Compounds - Tsikrika, Konstantina (Molecules, 2021)
HPP at 600 MPa alone, and in combination with US at 20 kHz (200 W), was applied to minimally processed potatoes of two commonly grown cultivars in Ireland. Changes in colour and microbial load (Enterobacteriaceae, total aerobic count, Salmonella, yeasts, and moulds) were monitored in vacuum-packaged potatoes during 14 days of storage at 4 °C. HPP and HPP/US significantly (p < 0.05) affected the colour parameters a*, b*, L*, and ΔE of minimally processed potatoes compared to the controls. Microbial growth was delayed in most of the treated samples with respect to those untreated (controls), while HPP completely inactivated Enterobacteriaceae in both cultivars. Total phenolic content and antioxidant activities were not altered in the treated samples of both varieties when compared to the controls. The levels of chlorogenic acid, ferulic acid, and caffeic acid were decreased after both treatments, with a significant (p < 0.05) increase in quinic acid in the treated samples as opposed to those untreated. A significant (p < 0.05) decrease in the levels of glycoalkaloids, namely α-chaconine and α-solanine, in HPP- and HPP/US-treated potatoes was also observed. These findings suggest that HPP and US can extend the shelf-life of minimally processed potatoes with a negligible impact on their antioxidant activity and phenolic content.